Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Voltaire's notebooks (Voltaire 81-82): thirteen new fragments, edited by Theodore Besterman Paul Ilie, The Voices in Candide's garden, 1755-1759: a methodology for Voltaire's correspondence Maureen F. O'Meara, Le Taureau Blanc and the activity of language Marlinda Ruth Bruno, Fréron, police spy Lloyd R. Free, Laclos and the myth of courtly love Lawrence Kerslake, Johann Georg Sulzer and the supplement to the Encyclopédie